Quantification of Sphingosine-1-Phosphate (S1P) in Patients with Periodontitis Stage II Grade B - María I. García-Parra (Odovtos - International Journal of Dental Sciences, 2022)
The aim of this study was the quantification of Sphingosine-1-phosphate (S1P) in periodontal pockets of patients with periodontitis. This is an observational, descriptive, case-control study. Thirty subjects were selected: 15 controls and 15 cases. A periodontal study was conducted following the parameters of AAP 2017 for the diagnosis of periodontal diseases. A sample of saliva and gingival crevicular fluid was obtained from each subject and then analyzed with the Human S1P Elisa kit (MyBioSource #MBS2516132) accordingly to the manufacturer's instructions, in order to verify the presence of S1P and quantify it´s concentration when founded. Results showed a significant difference (p=0.05) between cases and controls. In the case of saliva samples, the concentration of S1P was higher than the ones found in the control group (72.94 ng/mL and 45.12 ng/mL). For GCF, a higher amount of S1P was found in patients with POD (20.09 ng/mL and 15.20 ng/mL). This work raises a possible route of bone metabolism, inflammatory process, and identification of periodontitis through oral quantification of S1P, however, future studies are needed.